PENGARUH INSENTIF PAJAK BBN KB TERHADAP JUMLAH WAJIB PAJAK KENDARAAN BERMOTOR YANG TERDAFTAR DI SURABAYA BARAT - DWI APSARI, NOFANTI Dwi (Jurnal Akuntansi AKUNESA, 2012)
This research aims to determine the effect of tax incentives BBN KB to the number of registered taxpayers in West Surabaya. Effect of tax incentives BBN KB calculated by comparing the amount subject to tax before the tax incentive BBN KB policies with current policy BBN KB tax incentives put in place. This research using descriptive method. Conclude from this study is the effect of tax incentives BBNKB effect on increasing taxpayer registered motor vehicles in west Surabaya. Keywords: Tax incentives BBN KB, Taxpayers.